Disagreement-in-principle: Negotiating the right to practice Coast Salish culture in treaty talks on Vancouver Island, BC - Thom, Brian (University of British Columbia, 2008)
In negotiations to define the nature and scope of aboriginal rights, land ownership and self-government, British Columbia-based First Nations are asked to consider a clause setting out a right to practice their culture. When read in the full context of these proposed treaty agreements, the vision of the culture defined in this right is static and narrow, removing the constitutional protections for the complex and powerful social, political, economic dimensions of a more fully realized understanding of culture. This paper critically evaluates this proposed treaty right in the context of the long-standing processes of assimilation, and describes a more dynamic model of recognition and reconciliation of these cultural rights in treaties. Faculty Reviewed